Extracellular Vesicles from Akkermansia muciniphila Elicit Antitumor Immunity Against Prostate Cancer via Modulation of CD8+ T Cells and Macrophages - Luo ZW (Dove Medical Press, 2021)
Zhong-Wei Luo,1,2 Kun Xia,1,2 Yi-Wei Liu,1,2 Jiang-Hua Liu,1,2 Shan-Shan Rao,2,3 Xiong-Ke Hu,1,2 Chun-Yuan Chen,1,2 Ran Xu,4 Zhen-Xing Wang,1,2 Hui Xie1,2,5– 8 1Department of Orthopedics, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 2Movement System Injury and Repair Research Center, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 3Xiangya Nursing School, Central South University, Changsha, Hunan, People’s Republic of China; 4Department of Urology, The Second Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 5Department of Sports Medicine, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 6Hunan Key Laboratory of Organ Injury, Aging and Regenerative Medicine, Changsha, Hunan, People’s Republic of China; 7Hunan Key Laboratory of Bone Joint Degeneration and Injury, Changsha, Hunan, People’s Republic of China; 8National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Hui XieDepartment of Orthopedics, Xiangya Hospital, Central South University, 87 Xiangya Road, Changsha, Hunan, 410008, People’s Republic of ChinaEmail huixie@csu.edu.cnRan XuDepartment of Urology, The Second Xiangya Hospital, Central South University, 139 Middle Renmin Road, Changsha, Hunan, 410011, People’s Republic of ChinaEmail xuran@csu.edu.cnPurpose: Prostate cancer (PCa) is one of the most common malignancies in males. Despite the success of immunotherapy in many malignant cancers, strategies are still needed to improve therapeutic efficacy in PCa. This study aimed to investigate the effects of Akkermansia muciniphila-derived extracellular vesicles (Akk-EVs) on PCa and elucidate the underlying immune-related mechanism.Methods: Akk-EVs were isolated by ultracentrifugation and intravenously injected to treat syngeneic PCa-bearing immune-competent mice. Immunophenotypic changes in immune cells, such as cytotoxic T lymphocytes and macrophages, were measured via flow cytometry analysis. Histological examination was used to detect morphological changes in major organs after Akk-EVs treatments. In vitro, flow cytometry was performed to confirm the effects of Akk-EVs on the activation of CD8+ T cells. Quantitative PCR and immunofluorescence staining were carried out to test the impact of Akk-EVs on macrophage polarization. Cell counting kit-8 (CCK-8) analysis, colony formation assays, and scratch wound healing assays were conducted to assess the effects of Akk-EVs-treated macrophages on the proliferation and invasion of PCa cells. CCK-8 assays also confirmed the impact of Akk-EVs on the viability of normal cells.Results: Intravenous injection of Akk-EVs in immune-competent mice reduced the tumor burden of PCa without inducing obvious toxicity in normal tissues. This treatment elevated the proportion of granzyme B-positive (GZMB+) and interferon γ-positive (IFN-γ+) lymphocytes in CD8+ T cells and caused macrophage recruitment, with increased tumor-killing M1 macrophages and decreased immunosuppressive M2 macrophages. In vitro, Akk-EVs increased the number of GZMB+CD8+ and IFN-γ+CD8+ T cells and M1-like macrophages. In addition, conditioned medium from Akk-EVs-treated macrophages suppressed the proliferation and invasion of prostate cells. Furthermore, the effective dose of Akk-EVs was well-tolerated in normal cells.Conclusion: Our study revealed the promising prospects of Akk-EVs as an efficient and biocompatible immunotherapeutic agent for PCa treatment.Keywords: Akkermansia muciniphila, extracellular vesicles, immunotherapy, prostate cancer, cytotoxic T lymphocytes, macrophages